2020
DOI: 10.1021/acs.jpcc.0c02713
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Visualization of Commercial Lithium Ion Battery Cathodes: Distinguishing Between the Microstructure Components Using Atomic Force Microscopy

Abstract: The integration of lithium-ion batteries (LIB) into transportation through the implementation of hybrid and electric vehicles is driving fundamental research into improving their performance and lifetime. The rapid production of new electric vehicles by several popular brands also raises the question of how much material will eventually need to be reused or recycled. With a combination of an enhanced fundamental analysis of commercially utilized electrodes with fundamental chemical knowledge, answers to the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Studies by Demirocak et al revealed that mechanical degradation is due to a reduced crystallinity of PVDF, as indicated by a decreasing hardness and modulus of elasticity with age. 60,61 This can affect the electrode by reducing the adhesiveness of the binder to the active material and current collector (i.e. loss of contact).…”
Section: Microscopic Recycling Issuesmentioning
confidence: 99%
“…Studies by Demirocak et al revealed that mechanical degradation is due to a reduced crystallinity of PVDF, as indicated by a decreasing hardness and modulus of elasticity with age. 60,61 This can affect the electrode by reducing the adhesiveness of the binder to the active material and current collector (i.e. loss of contact).…”
Section: Microscopic Recycling Issuesmentioning
confidence: 99%
“…Here, the AFM scan produces modulus data through the probe coming into contact with the surface until a set point is reached, generating a force–time curve for every pixel on the image. Terreblanche et al used this technique to identify the different electrode components for NMC cathodes, and the same technique and modulus models were used in this study . It should be noted that the modulus images show a semiquantitative, comparative contrast in the modulus values; quantitative values for the modulus could not be acquired for these samples.…”
Section: Resultsmentioning
confidence: 99%
“…In this mode, the probe comes into contact with the surface until a specified force set point is reached, generating a force versus time curve for every pixel of the image allowing modulus values to be generated from these curves. This allows for the identification of the different electrode components on the surface, as done previously for NMC by Terreblanche et al 36 A RTSEP-300 probe with a spring constant of 40 N/m was used to acquire the height images and data used by the Nanoscope 16.4 software to calculate the Sneddon Modulus, giving a modulus scan of the surface. Scratch testing was carried out using a ST200 scratch tester with a diamond probe.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate metal removal/precipitation from vehicular battery leachates, two commercial LIB cathodes (Nissan Leaf) were leached with two different mineral acids, H2SO4 or HCl, both widely used in hydrometallurgy. 18 These cathode materials contained either Li, Ni, Mn and Co in a ratio of 50% nickel, 30% manganese, and 20% cobalt (NMC-532), or a mixture of approximately 70% lithium manganese oxide spinel (LMO) with 25% lithium nickel manganese cobalt oxide 19 , referred to hereafter as A1C and B1C, respectively. The concentration of metals (Al, Co, Mn, Li and Ni) in these LIB leachates was dependent upon the origin of the cathode material, solvent used and leaching temperature (ESI, Table S1).…”
Section: Selective Bioprecipitation Of Dissolved Mn From Vehicular Li...mentioning
confidence: 99%